Experimental Studies on PV Module Cooling With Radiation Source PCM Matrix - Karthikeyan Velmurugan (IEEE, 2020)
Rise in PV module temperature ( $\text{T}_{PV}$ ) majorly drops the electrical output of the PV system. This research presents a novel cylindrical tube PCM matrix that is not in physical contact with the PV module back surface unlike the existing PCM based PV module cooling techniques. This contactless PCM matrix prevents the PV module from thermal and physical stress, also it blocks thermal energy re-conduction from PCM to PV module. While stored thermal energy from PCM retransferred to the PV module during off-sunshine hours and also when the PCM turns to liquid $\text{T}_{PV}$ starts to rise abruptly, this contactless PCM matrix minimizes these issues as PCM matrix receives thermal energy by the mode of radiation and convection; Besides, PCM matrix surface area is not enclosed with the PV module back surface area that reduces the thermal stress and re-conduction. Developed PCM matrix is integrated beneath the PV module at particular distances of 6 mm, 9 mm and 12 mm to optimize the spacing between PV module and PCM matrix. It is found that 6 mm spacing PCM matrix reduced the $\text{T}_{PV}$ maximum of 2.5 °C compared to 9 mm and 12 mm spacing. This $\text{T}_{PV}$ reduction enhanced the PV module electrical output by 0.2 % than PV without PCM and it is observed that 6 mm is an optimal spacing for the radiation source PCM matrix.